On Rainbow Coloring of Quadrilateral Snake Graphs - Wendt, Felipe B.; Rocha, Aleffer; Omai, M. M. (Anais do Encontro de Teoria da Computação (ETC); 2026: Anais do XI Encontro de Teoria da Computação, 2026)
A path is said rainbow if its edges have pairwise distinct colors. A graph G admits a rainbow coloring if there exists a rainbow path between every pair of vertices of G. When such a path is a shortest path, we say that G has a strong rainbow coloring. The rainbow connection number rc(G) (respectively, the strong rainbow connection number src(G)) is the minimum number of colors required to obtain a (strong) rainbow coloring of G. In this work, we determine rc(G) and src(G) when G is a quadrilateral snake graph. We also determine rc(G) when G is a double quadrilateral snake graph.